Predicting Career Success of Graduate Business School Alumni - Gutteridge, Thomas G. (Academy of Management Journal, 1973)
Factors related to the career progress of graduate business school alumni were studied. Individuals with full-time work experience prior to enrolling are progressing faster in their careers. Alumni employed in the engineering- production function are earning lower salaries. There is a negative relationship between company size and salaries. Alumni who have changed functional areas or employers are receiving higher salaries.